Exploring the Therapeutic Potential of Kalanchoe Pinnata: A Comprehensive Analysis of Bioactive Compounds and Pharmacological Activities - Bhusal, Dakshina; Poudel, Manila; Tamang, Ashika; Dhital, Sujan; Parajuli, Nirmal; Shrestha, Timila; Bharati, Samjhana; Maharjan, Binita; Adhikari Subin, Jhashanath; Marasini, Bishnu Prasad; Shrestha, Ram Lal Swagat (Biology, Medicine, & Natural Product Chemistry, 2024)
Natural products are vital in drug discovery for their bioactive compounds. This study evaluated Kalanchoe pinnata's leaf extracts for antidiabetic, antimicrobial, antioxidant, and cytotoxic properties. GC-MS identified seven components in hexane and twenty in methanol extracts. The ethyl acetate extract had high phenolic (485.17 mg GAE/g) and flavonoid (40.25 mg QE/g) contents. Methanol extract showed strong antioxidant (IC50: 293.53 µg/mL) and anti-alpha glucosidase (IC50: 195.39 µg/mL) activity. Antimicrobial tests showed varied effectiveness, while chloroform and acetone extracts exhibited notable cytotoxicity. ADMET predictions assessed absorption and blood-brain barrier penetration, highlighting K. pinnata's potential for drug development.